2005
DOI: 10.3892/ijmm.15.3.443
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms for microsomal epoxide hydrolase and genetic susceptibility to COPD

Abstract: Although smoking is the major causal factor in the development of chronic obstructive pulmonary disease (COPD), only 10-20% of chronic heavy cigarette smokers develop symptomatic COPD, which suggests the presence of genetic susceptibility. The human microsomal epoxide hydrolase (EH) is a metabolizing enzyme which involves the process of numerous reactive epoxide intermediates and contains polymorphic alleles which are associated with altered EH activity and may be linked to increased risk for COPD. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 24 publications
(38 reference statements)
1
35
1
Order By: Relevance
“…They do not find any effect on the risk of COPD for either the T113C or the A139G polymorphisms. [13] HERSH [28] FU [27] BRØGGER [2] CHENG [26] PARK [25] ZIDZIK [24] VIBHUTI [23] MATHESON [22] KORYTINA [20] BUDHI [19] RODRIGUEZ [18] XIAO [17] TAKEYABU [16] YIM [15] PARK [14] SMITH [21] CHAPPELL [7] Overall . Meta-analysis of EPHX1 A139G genotype and risk of chronic obstructive pulmonary disease (COPD); overall and stratified analyses using both random and fixed effect models.…”
Section: Copdmentioning
confidence: 99%
See 1 more Smart Citation
“…They do not find any effect on the risk of COPD for either the T113C or the A139G polymorphisms. [13] HERSH [28] FU [27] BRØGGER [2] CHENG [26] PARK [25] ZIDZIK [24] VIBHUTI [23] MATHESON [22] KORYTINA [20] BUDHI [19] RODRIGUEZ [18] XIAO [17] TAKEYABU [16] YIM [15] PARK [14] SMITH [21] CHAPPELL [7] Overall . Meta-analysis of EPHX1 A139G genotype and risk of chronic obstructive pulmonary disease (COPD); overall and stratified analyses using both random and fixed effect models.…”
Section: Copdmentioning
confidence: 99%
“…[2,7,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]) investigating the EPHX1 T113C and A139G polymorphisms in relation to COPD or emphysema as the primary end-point were included. Two minor studies were excluded from the analyses, because we were unable to retrieve the original papers despite contacting the corresponding authors.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In addition, a comparison of patients with severe COPD to those with mild-to-moderate disease revealed that the frequency of the homozygous His113His mEPHX exon 3 variant was significantly higher in severe COPD (Cheng et al 2004). In the study by Park et al (2005), a significantly increased risk for COPD was observed for subjects with the mEPHX (His113His) genotypes. On the other hand, two studies failed to demonstrate an association between low activity variant of mEPHX and COPD Zhang et al 2002).…”
Section: Microsomal Epoxide Hydrolasementioning
confidence: 99%
“…Most of the studies reported significant associations between low mEPHX activity genotypes and the risk for COPD Sandford et al 2001;Rodriguez et al 2002;Xiao et al 2003;Cheng et al 2004;Park et al 2005). In the study by Sandford et al (2001), a combination of a family history of COPD together with a homozygosity for the His 113 /His 139 haplotype in the mEPHX gene was associated with rapid decline of lung function.…”
Section: Microsomal Epoxide Hydrolasementioning
confidence: 99%
“…These studies included 9 Caucasian populations (Rodriguez et al, 2002;Korytina et al, 2003;Hersh et al, 2005;Park et al, 2005;Brøgger et al, 2006;Chappell et al, 2008;Židzik et al, 2008;Penyige et al, 2010;Lee et al, 2011) and 10 Eastern Asian populations (Takeyabu et al, 2000;Yim et al, 2000;Yoshikawa et al, 2000;Zhang et al, 2002;Budhi et al, 2003;Park et al, 2003;Cheng et al, 2004;Xiao et al, 2004;Fu et al, 2007;Hua et al, 2012) ( Table 1). The total number of samples in the Caucasian and Eastern Asian populations were 47,048 (6471 cases vs 40,577 controls) and 2586 (1228 cases vs 1358 controls), respectively.…”
Section: Literature Searchmentioning
confidence: 99%